Absorptive frequency selective surface using parallel LC resonance. Issue 6 (1st March 2016) - Chen, Qiang; Liu, Liguo; Chen, Liang; Bai, Jiajun; Fu, Yunqi
Abstract : A frequency selective surface with absorptive/ transmissive property is represented. It allows waves at high frequency around 10 GHz to transmit with very low insertion loss by using the resonance between a parallel microstrip LC structure. It also possesses a wide absorption over lower band by inserting lumped resistors into elements. The absorption band is over 3–9 GHz. A prototype is fabricated and its absorptive/ transmissive performance is measured.